Functional Capacity Improvement Related to Inflammatory Marker Reduction After Phase II Cardiac Rehabilitation Program in Postrevascularization Coronary Artery Disease Patients - Badai B. Tiksnadi; Melisa Aziz; Manda S. Chesario; Mochamad Renaldi; Ahmad Triadi; Sunaryo B. Sastradimaja; Augustine Purnomowati; Toni M. Aprami (ACI (Acta Cardiologia Indonesiana), 2019)
Background: Improved functional capacity (FC) and inflammatory marker reduction is a good prognostic factor in post-revascularization cardiac patients. However, there is still limited study investigated association of functional capacity and inflammatory marker after cardiac rehabilitation program. We studied the effects of cardiac rehabilitation (CR) program in the improvement of FC and high-sensitive-C Reactive Protein (hs-CRP) reduction and association between those variables.Methods: This was quasi experimental study in post-revascularization CAD patients who attended phase II CR program at CR gymnasium, Dr. Hasan Sadikin General Hospital, Bandung, from October 2014 to May 2015. The CR program included additional education sessions and consistently strict program intensity on 50-80% heart rate reserve based on formula and Borg scale 11 to 15. Functional capacity and hsCRP were measured before and after the program. Functional capacity was assessed by maximal treadmill test through indirect VO2 max measurement.Results: A total of 37 patients aged 56.05±7.3 years old were analyzed in this study. They consisted mainly of men (81.1%) which 78.4% of them underwent percutaneous coronary intervention (PCI). Our study revealed significant FC improvement after completion of this newly-modified CR program from an average of 6.76 to 8.68 METs (28.4%) ( p<0.001). Hs-CRP reduction was also occurred from mean of 0.49 mg/L to 0.20 mg/L (59.2%) of log hs-CRP level (p= 0.005). Linear regression analysis showed the improvement of fitness was associated with baseline FC (p<0.001) and reduction of hs-CRP was associated with baseline hs-CRP (p<0.001), and not influenced by age, gender, ejection fraction and type of procedure. There is moderate correlation (rs= 0.636, p<0.001) between functional capacity improvement and hs-CRP reduction. Each 1 METs improvement can reduce 9.317 mg/L of transformed hs-CRP level (p=0.006, 95%CI 2.942,15.693).Conclusions: CR program significantly increased functional capacity and reduce hsCRP level in post-revascularization CAD patient, and more prominent in a patient with low baseline functional capacity and high hs-CRP level. Functional capacity improvement and hs-CRP reduction were moderately correlated.